Medicinal Plants in Traditional Herbal Wines and Liquors in the East of Spain and the Balearic Islands - Martínez-Francés, V.; Rivera, D.; Obon, C.; Alcaraz, F.; Ríos, S. (Frontiers in Pharmacology, 2021)
Homemade herbal preparations from the East of Spain, are the witness of traditional medicine inherited from the ancient complex formulas of herbal teas and medicinal wines. In this study we document the use of traditional alcoholic beverages, identify their ingredients, almost exclusively botanical, record the local medicinal uses of these mixtures and discuss patterns of distribution of this knowledge in regions of eastern Spain, the Balearic Islands and Andorra. We determine marker species and relevant patterns of herbal formulas in the different regions of the territory. Homemade liquors and liqueurs are consumed for their digestive and tonic-restorative properties but they also play in some cases an important social role. The elderly remember other medicinal uses such as aperitif, emmenagogue or antidiarrheal, for some of the most popular preparations. The herbal liqueur formulas include predominantly Lamiaceae, Asteraceae, Rosaceae, Rutaceae and Apiaceae species. Herbs (58%), fruits (28%) and mixtures of both (12%), are ingredients of liquors and wines, being the aerial parts the most frequent in terms of species (30%) and records (49%). Dictamnus hispanicus, Santolina villosa, Salvia blancoana subsp. mariolensis, Rosmarinus officinalis, Thymus vulgaris, Clinopodium serpyllifolium subsp. fruticosum are the species most frequently used. Others species used to a lesser extent as Polygonatum odoratum, Thymus moroderi and Saxifraga longifolia are restricted to locally homemade preparations because their collection and uses require a special knowledge of the rare or endemic flora. Sustainability of these practices is strongly limited by the overall loss of local traditional knowledge and by the limited availability of most of the wild species, some of them endangered or threatened mainly by the loss of their natural habitats. Cultivation and domestication are a promising alternative for what Thymus moroderi cultivation in Alicante province and Polygonatum odoratum in Teruel province are examples. There is a notable decrease in the complexity of the formulas registered throughout the nearly fifteen years of the study. This is interpreted as a consequence of a loss of knowledge, less accessibility to wild resources and changes in traditions and preferences.